Rehabilitation of juvenile offenders (III) (Journal of Parents and Teachers, 2025)
The article presents the idea that love and discipline must go hand in hand in education. It also states that without an educational project, there is no education or re-education, as the objectives, recipients, agents, and modalities are unclear. This is because it is not planned, organized, motivated, or controlled.